Geotectonics and Exploration of Gold Mineralization in the Kushaka-Kusheriki Schist Belt North-Central Nigeria - Okpoli, Cyril C.; Idakwo, Sunday O.; Olaniyan, Oladele; Chidi, Promise E. (Indonesian Journal of Earth Sciences, 2025)
The lack of systematic and organized development and exploration for gold and increasing demand for sustainable development goals has prompted the integrated geological, geophysical and geochemical surveys to characterize the gold mineralization at Owu part of the Kushaka-Kusheriki schist belt in North Central Nigeria. Previous studies concentrated on geology and geochemical studies with no emphasis on the use of integrated studies and state-of-the-art tools aimed at characterizing gold mineralization. Detailed geological mapping was carried out to determine the various rock types and their structural framework. Thirty- one (31) data were acquired using Proton Precession Magnetometer for geophysical survey to delineate their degree of magnetic susceptibility and dataset was enhanced using Fast Fourier Transforms (FFT). Inductively Coupled Plasma/Optical Emission Spectrometry (ICPOES), fire assay, multi-acid digestion with gravimetric method were carried out on rocks and soils to determine their geochemical signatures. Geologically, the study area consists of phyllite, mica schist, amphibole schist, phyllitic schist, biotite schist within schist shear zone. Structurally, granitic intrusions are observed in the NE-SW direction, parallel to the regional foliation of the rocks. Geophysical data were subjected to different forms of filtering, which showed high and low magnetic areas. The results reveal a distinct tectonic activity that led to shearing and fracturing, and subsequently gave rise to a structurally controlled mineralization pattern (i.e., NE-SW direction in the Pan African domain).  ICPOES analysis yielded Au concentration of <0.2 – 201 ppm with 80% of the soil samples exceeding 2 ppm indicating their qualification as ores. The soil samples are enriched in W (1 – 241 ppm), Mo (1 – 19.8 ppm) but depleted in Sb (<5) and Ag (<2 ppm). Positive correlations between Au and Cu, Zn and Pb confirm that they are pathfinder elements for Au in the area. The geological and geophysical studies reveal structurally controlled mineralization; while the very low K/Ba (<0.01) suggests non- structurally controlled gold mineralization in sediments occasioned by dispersion of the metals. The integrated approach has proved effective in delineating gold mineralized zones, and is recommended for other related investigations.